An Analysis of Grammatical Errors in Song Lyrics - Uktolseja, Lulu Jola (INTERACTION: Jurnal Pendidikan Bahasa, 2020)
Learning English is important in this era. English as an international language will be used globally to build up the relation and connection with the other countries. English has a lot of grammar elements that are very important to note in order to be used appropriately. In Indonesian, we do not know so many grammatical elements so that when learning English mistakes in grammar are common. It also becomes very critical if English learners cannot distinguish every word or sentence that is heard through movie or music. This research is a descriptive research. In this research, the data is a kind of text, thus the writer uses the documentation technique. The steps of doing this research are: Identifying, Classifying, Interpreting, Describing, and Concluding: the writer finds the conclusion and gives the suggestions. The result of this research, there are several grammatical errors in songs such as Conditional Sentence, Subject-Verb Agreement, Pronoun, Negator and Auxiliary Verbs.